Leisure Crafting and Life Satisfaction in Muslim Young Adults: The Mediating Role of Islamic Well-Being - Mehmet Demirel; Ça?r? Saraçl?; Andaç Akçakese (Utan Kayu Publishing, 2025)
This study examines the relationship between leisure crafting and life satisfaction among Muslim young adults, focusing on the mediating role of Islamic well-being. While leisure crafting's benefits for psychological well-being are known, its intersection with spiritual well-being in Islamic contexts is underexplored. The study involved 328 participants aged 18-24 from Turkey. Data were collected through online and face-to-face surveys. Confirmatory factor analysis, reliability analysis, and multiple regression were used. Results indicated significant positive effects of leisure crafting on life satisfaction and Islamic well-being. Islamic well-being was found to mediate the relationship between leisure crafting and life satisfaction, highlighting the importance of integrating spiritual dimensions into leisure activities. The study highlights the importance of integrating spiritual dimensions into leisure activities for enhancing life satisfaction. It provides insights for designing culturally and spiritually sensitive leisure programs to promote overall well-being in Islamic contexts.